Réponse :
On commence par tout mettre sur le même dénominateur.
[tex]E=(\frac{3*3}{5*3}-\frac{5*3}{3*5} ) / \frac{7}{2} -(\frac{5*3}{1*3} -\frac{2*1}{3*1} )[/tex]
[tex]E=(\frac{9}{15}-\frac{25}{15} ) / \frac{7}{2} -(\frac{15}{3} -\frac{2}{3} )[/tex]
[tex]E=(-\frac{16}{15} ) / \frac{7}{2} -(\frac{13}{3} )[/tex]
[tex]E=(-\frac{16*2}{15*7} )-(\frac{13}{3} )[/tex]
[tex]E=-\frac{32}{105} -\frac{13}{3}[/tex]
[tex]E=-\frac{32*3}{105*3} -\frac{13*105}{3*105}[/tex]
[tex]E=-\frac{96}{315} -\frac{1365}{315}[/tex]
[tex]E=-\frac{96-1365}{315}[/tex]
[tex]E=-\frac{487}{105}[/tex]
Explications étape par étape :